Do Children Recall Numbers as Generic? A Strong Test of the Generics-As-Default Hypothesis. Issue 3 (3rd July 2019) - Gelman, Susan A.; Leslie, Sarah-Jane; Gelman, Rochel; Leslie, Alan
ABSTRACT: A striking characteristic of human thought is that we form representations about abstract kinds (Giraffes have purple tongues), despite experiencing only particular individuals (This giraffe has a purple tongue). These generic generalizations have been hypothesized to be a cognitive default, that is, more basic and automatic than other forms of generalization, including those involving quantifiers such as "all" or "most." In support of this hypothesis, children often recall quantified statements (e.g., "All/many/most bears climb trees") as generic ("Bears climb trees"), and do so more frequently than the reverse error of recalling generics as quantified. The present study provides a strong test of the generics-as-default position by testing whether even numerically quantified statements (e.g., "Five giraffes have purple tongues") are recalled as generic. Two groups of three-year-old children ( N = 74) were tested: those who held a correct numerical interpretation of five ("5-knowers"), and those who did not ("non-5-knowers"). Results indicate that non-5-knowers often defaulted to the generic in recall after hearing a number (e.g., recalling "Five giraffes." as "Giraffes."), whereas 5-knowers did not. Thus, consistent with the generic-as-default hypothesis, before children have a specific numerosity assigned to "five, " they display a tendency to recall numerically quantified phrases as generic.